A Ma10 gene encoding P‐type ATPase is involved in fruit organic acid accumulation in apple. Issue 3 (1st November 2018) - Ma, Baiquan; Liao, Liao; Fang, Ting; Peng, Qian; Ogutu, Collins; Zhou, Hui; Ma, Fengwang; Han, Yuepeng
Summary: Acidity is one of the main determinants of fruit organoleptic quality. Here, comparative transcriptome analysis was conducted between two cultivars that showed a significant difference in fruit acidity, but contained homozygous non‐functional alleles at the major gene Ma1 locus controlling apple fruit acidity. A candidate gene for fruit acidity, designated M10, was identified. The M10 gene encodes a P‐type proton pump, P3A ‐ATPase, which facilitates malate uptake into the vacuole. The Ma10 gene is significantly associated with fruit malate content, accounting for 7.5% of the observed phenotypic variation in apple germplasm. Subcellular localization assay showed that the Ma10 is targeted to the tonoplast. Overexpression of the Ma10 gene can complement the defect in proton transport of the mutant YAK2 yeast strain and enhance the accumulation of malic acid in apple callus. Moreover, its ectopic expression in tomato induces a decrease in fruit pH. These results suggest that the Ma10 gene has the capacity for proton pumping and plays an important role in fruit vacuolar acidification in apple. Our study provides useful knowledge towards comprehensive understanding of the complex mechanism regulating apple fruit acidity.